Statistical modelling Of HIV/AIDS epidemic in the North Central zone Of Nigeria (2007)
The objective of this work were to apply the UNAIDS Estimation and Projection Package (EPP) to HIV/AIDS epidemic in the north central zone of Nigeria, to propose a statistical model for the course of the epidemic in the zone and to generally investigate the level of trend inherent in the epidemic, over the years. We used HIV/AIDS surveillance data to model the situation for the rural and urban sentinel sites in the zones. Using the EPP as our point of reference, we proposed a statistical model (based on modifications made to the original back calculation methods) for the course of HIV/AIDS epidemic in the zone. Our result shows that the UNAIDS package is a great AID to HIV/AIDS modeling in Nigeria. The incidence rate was estimated to be 0.91 in 1997, 0.7% in 2000 and projected to be 0.63 in 2010. Also an estimated 378,870 people are expected to die due to the epidemic in the year 2010. The prevalence peaked later than the incidence which peaked around 1997, but this is expected to rise slowly after 2007. The mortality rate is relatively low among sites inside major towns (IMT) than those outside major town (OMT), but the situation is generally still on the rise.